Pengaruh Edukasi Kesehatan Melalui Video terhadap Pengetahuan Masa Pubertas pada Remaja Putri di SMP Negeri 1 Banguntapan - Herniawati, Siska; Hakim, Riska Ismawati; Agustiani, Mia Dwi (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2025)
Background: According to data from the Yogyakarta Central Statistics Agency (BPS) in 2023, the total population reached 413,623 people, with 51% consisting of females aged 10–15 years. In the same year, there were 255 cases of adolescent childbirths in the Special Region of Yogyakarta, an increase from the previous year. Most cases occurred among adolescents aged 15–17 years. Bantul and Sleman regencies reported the highest number of cases, with 72 cases each (28.2%). Bantul had the highest number of adolescent childbirths among 15–17-year-olds, with 47 cases (21.5%), particularly in Banguntapan Subdistrict, which recorded 18 cases (11.7%). This situation highlights the need for early educational interventions. This study aims to determine the effect of health education using video media on improving knowledge about puberty among adolescent girls. Methods: This study employed a quasi-experimental design with a two-group pre-test and post-test approach. The sample consisted of 63 seventh-grade female students selected using stratified random sampling: 32 students in the intervention group received health education via a 10-minute video shown twice, while 31 students in the control group received a 16-minute lecture. The instrument used was a questionnaire that had undergone validity and reliability testing. Data were analyzed using the Wilcoxon and Mann-Whitney tests. Results: The average knowledge score in the video group increased from 60.7 to 87.9. In the control group, it increased from 58.1 to 68.5. Statistical analysis showed p < 0.05, indicating a significant effect of video media in increasing puberty knowledge. Conclusion: Health education using video media is effective in improving puberty knowledge among adolescent girls.